Effect of price escalation on highway construction projects - Walawage, Ranjith Palitha Ahangama; Karasudhi, Pisidhi; Ping Kunawatsatit; Wireland, Martin (Bangkok : Asian Institute of Technology, 1983)
This study is to emphasize the financial problems caused by escalation of prices in highway construction projects. Through the review of the current trends of escalation and the existing escalation models, a more reliable model is developed to estimate the amount of escalation. The statistics of five highway and one expressway construction projects are used to develop the new model. Past prices of major resource items are used to obtain the prediction curves by polynomial regression analysis, which may be useful to forecast future costs in fixed price contracts. Results by the new model are compared with those by the two models used in the Department of Highways of Thailand. Effects of the price escalation on cash flows and working capital of projects are investigated, and procedures for cost adjustments as project are presented. Finally, the influence of inflation on the depreciation allowance and the resulting losses are examined.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Road construction -- Cost effectiveness